Coping with advantageous inequity: Field evidence from professional penalty kicking - Mario Lackner; Hendrik Sonnabend (Johannes Kepler University of Linz, Department of Economics, 2017)
This contribution examines the effect of advantageous inequity on performance using data from top-level penalty kicking in soccer. Results indicate that, on average, professionals do not perform worse when they experience unfair advantages. However, we find a negative effect of advantageous inequity in situations where success is less important.
Keywords: C93; D91; Z29; 330; advantageous inequity; guilt; self-serving bias; fairness; performance